Determination of oscillator strength of confined excitons in a semiconductor microcavity - Cotta, E.A.; Roma, P.M.S. (Condensed Matter Physics, 2014)
We have achieved a significant experimental Rabi-splitting (3.4 meV) for confined polaritons in a planar semiconductor λ microcavity for only a single quantum well (SQW) of GaAs (10~nm) placed at the antinode. The Rabi-splitting phenomena are discussed in detail based on the semiclassical theory, where two coupled harmonic oscillators (excitons and photons) are used to describe the system. In this way, we can obtain the dispersion curve of polaritons, the minimum value for the cavity reflectance and the oscillator strength to reach the strong coupling regime. This approach describes an ensemble of excitons confined in a SQW and includes a dissipation component. The results present a weak coupling regime, where an enhanced spontaneous emission takes place, and a strong coupling regime, where Rabi-splitting in the dispersion curve can be observed. The theoretical results are confronted with experimental data for the reflectance behavior in resonant and off-resonant conditions and present a great accuracy. This allows us to determine the oscillator strength of the confined excitons in the SQW with great precision. Нами досягнуто значного експериментального розщеплення Рабi (3.4 меВ) для обмежених поляритонiв у плоскому напiвпровiдниковому λ мiкрорезонаторi для одиночної квантової ями GaAs (10 нм), розмiщеної в антивузлi. Явище розщеплення Рабi детально обговорюється на основi напiвкласичної теорiї, коли для опису системи використовуються два зв’язанi гармонiчнi осцилятори (екситони i фотони). В такий спосiб можна отримати дисперсiйну криву поляритонiв, мiнiмальне значення для коефiцiєнта вiдбивання резонатора i силу осцилятора для досягнення сильнозв’язаного режиму. Цей пiдхiд описує ансамбль екситонiв обмежених одною квантовою ямою i враховує дисипацiю. Результати представляють як слабозв’язаний режим з посиленням спонтанної емiсiї, так i сильнозв’язаний режим, коли спостерiгається розщеплення Рабi на дисперсiйнiй кривiй. Теоретичнi результати порiвнюються з експериментальними даними для поведiнки коефiцiєнта вiдбивання в резонансних i нерезонансних умовах i є дуже точними. Це дозволяє з високою точнiстю визначити силу осциляторiв обмежених однiєю квантовою ямою екситонiв.